Analysis of Wave Solutions of an Adhenovirus-Tumor Cell System - Baba Issa Camara; Houda Mokrani (Abstract and Applied Analysis)
We discuss biological background and mathematical analysis of glioma gene therapy for contributing to cancer treatment. By a reaction-diffusion system, we model interactions between gliom cells and viruses. We establish some sufficient conditions on model parameters which guarantee the permanence of the system and the existence of periodic solutions. Our study has experimental and theoretical implication in the perspective management strategy of therapy.